π-Lewis Base Activation of Carbonyls and Hexafluorobenzene - Mondal, Aditesh; Breitwieser, Kevin; Danés, Sergi; Grünwald, Annette; Heinemann, Frank Wilhelm; Morgenstern, Bernd; Müller, Frank; Haumann, Michael; Schütze, Maximilian; Kass, Dustin; Ray, Kallol; Munz, Dominik (Angewandte Chemie International Edition, 2025)
We report hitherto elusive side-on η2-bonded palladium(0) carbonyl (anthraquinone, benzaldehyde) and arene (benzene, hexafluorobenzene) palladium(0) complexes and present the catalytic hydrodefluorination of hexafluorobenzene by cyclohexene. The comparison with respective cyclohexene, pyridine and tetrahydrofuran complexes reveals that the experimental ligand binding strengths follow the order THF<C6H6<C6F6<cyclohexene<pyridine<benzaldehyde<anthraquinone. To understand this surprising order, the complexes’ electronic structures were elucidated by nuclear magnetic resonance (NMR), single crystal X-Ray diffraction (sc-XRD), ultraviolet/visible (UV/Vis) electronic absorption, infrared (IR) vibrational, Pd L3-edge X-ray absorption (XAS), and X-ray photoelectron (XP) spectroscopic techniques, complemented by Density Functional Theory (DFT) calculations including energy decomposition (EDA-NOCV) and effective oxidation state (EOS) analyses. For benzene, pyridine and cyclohexene, bonding follows the donor/acceptor picture of the Dewar–Chatt–Duncanson model. In stark contrast, hexafluorobenzene, benzaldehyde and anthraquinone bind via essentially the π-channel only and thus as π-analogues of Z-acceptor ligands. This contribution elucidates the control of functional-group selectivity in palladium(0) catalysis and delineates a novel strategy to activate electron-deficient π-systems.
CRIS-Team Scopus Importer:2025-01-31
Keywords: Catalysis; Chemical Bonding; Intermediates; Organometallic Chemistry; Spectroscopy